Failure of recovery from lead induced hepatoxicity and disruption of erythrocyte antioxidant defence system in Wistar ratsTemidayo (2014)
Lead acetate (PbA) is one of the major environmental contaminants with grave toxicologicalconsequences both in the developing and developed countries. The liver and erythrocyteantioxidant status and markers of oxidative were assessed. Exposure of rats to PbA ledto significant decline (p < 0.05) in hepatic and erythrocyte glutathione peroxidase (GPx),glutathione S-transferase (GST), catalase (CAT), superoxide dismutase (SOD), and reducedglutathione (GSH) content. Similarly, malondialdehyde (MDA) and H2O2concentrations weresignificantly (p < 0.05) elevated. Histopathology and immunohistology of liver of rats exposedto PbA showed focal areas of necrosis and COX-2 expression after 6 weeks of PbA withdrawal.Taken together, hepatic and erythrocytes antioxidant defence system failed to recover afterwithdrawal of the exposed PbA for the period of the study. In conclusion, experimentalanimals exposed to PbA did not recover from hepatotoxicity and disruption of erythrocyteantioxidant defence system via free radical generation and oxidative stress.